Od konspiracji do kapitulacji - Skowronek, Jerzy (Warszawa : Krajowa Agencja Wydawnicza, 1989)
An history of the revolutionary movement in Poland in the first half of the 19th century.
Cover title.
Includes bibliographical references (p. 74-75).
Keywords: Revolutionaries -- Poland; Poland -- History -- 1830-1864.